2011
DOI: 10.1007/s10822-011-9443-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanics study of the hydroxyethylamines–BACE-1 active site interaction energies

Abstract: The identification of BACE-1, a key enzyme in the production of Amyloid-β (Aβ) peptides, generated by the proteolytic processing of amyloid precursor protein, was a major advance in the field of Alzheimer's disease as this pathology is characterized by the presence of extracellular senile plaques, mainly comprised of Aβ peptides. Hydroxyethylamines have demonstrated a remarkable potential, like candidate drugs, for this disease using BACE-1 as target. Density Functional Theory calculations were employed to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Thus, designing inhibitors that are capable of forming those vital anchor point interactions with BACE1 and maintaining this interaction over time is crucial to yield the best possible inhibitory activity. It was observed that the protonation status of hydroxyethyl amines could be shifted with time resulting in loss of essential interactions with BACE1 residues shifting the flap confirmation from the active (closed) back to the open form . Therefore, this shift in the flap confirmation can explain how some HEAs derivatives would fail to inhibit the BACE1 activity in real time.…”
Section: Failure Of Bace1 Inhibitors: Lessons To the Futurementioning
confidence: 99%
“…Thus, designing inhibitors that are capable of forming those vital anchor point interactions with BACE1 and maintaining this interaction over time is crucial to yield the best possible inhibitory activity. It was observed that the protonation status of hydroxyethyl amines could be shifted with time resulting in loss of essential interactions with BACE1 residues shifting the flap confirmation from the active (closed) back to the open form . Therefore, this shift in the flap confirmation can explain how some HEAs derivatives would fail to inhibit the BACE1 activity in real time.…”
Section: Failure Of Bace1 Inhibitors: Lessons To the Futurementioning
confidence: 99%
“…These plaques consist of aggregated amyloid--peptide (A ) deposits, -protein aggregation, oxidative stress, dyshomeostasis of biometals, and low acetylcholine (ACh) levels and plays significant role in the pathophysiology of the disease [7]. Nowadays, the most used therapeutic treatment against AD involves the use of acetylcholinesterase inhibitors (AChEIs) that improve AD symptoms by AChE inhibition [8][9][10][11][12]. The reversible AChE inhibition has become the promising target for the treatment of AD which is mainly associated with low in vivo AChE levels.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, smaller, approximate models can be used at higher levels of QM theory to evaluate particular regions of interest more rapidly. [41][42][43][44] Each of the methods discussed above offers distinct advantages in particular circumstances. For example, MM methods are very quick to evaluate, meaning extensive sampling is possible.…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods are available to predict the strength of interaction of individual functional groups which can prove extremely insightful in the design and modification of lead series. 41,43,44,[49][50][51] In this work we consider the use of small QM models of receptors, consisting of the key polar active site interactions, rather than generic probes. The region selected is not as extensive as used in the approach of Gueto-Tettay, who used residues within 5 Å of the active site, which, due to the significant size, necessitates the use of the semi-empirical PM6 method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation